The role of sleep in the formation and updating of abstract mental representations. (2020) - Visalli, Antonino; Cellini, Nicola
Abstract: According to Gilead and colleagues, to be efficient abstraction requires a hierarchical organization of information into long-term memory. But, how and when are abstract representations consolidated into long-term memory and how are they integrated with pre-existing abstracta are questions not discussed by Gilead and colleagues. Here, we propose that these processes occur preferentially during offline periods such as sleep.